Exposure to Biased Language: The Role of Linguistic Abstraction in the Transmission, Maintenance, and Formation of Beliefs - Collins, Katherine Anne (Université d'Ottawa / University of Ottawa, 2015)
Language plays an indispensable role in the transmission, maintenance, and formation of culturally shared beliefs. Yet beliefs about groups, in particular, are shared despite the existence of prohibitive norms that act to inhibit their expression. This apparent incongruity suggests that cultural beliefs become shared through linguistic means other than explicit expression. In support of this, the linguistic bias paradigm proposes that linguistic bias is the implicit and unintentional expression of beliefs through the differential use of linguistic abstraction (Franco & Maass, 1996; Maass, 1999; Maass, Salvi, Arcuri, & Semin, 1989), as defined by the Linguistic Category Model (Semin & Fiedler, 1988). According to this paradigm, linguistic bias not only reveals the speakers’ privately held beliefs but also transmits these beliefs to recipients, leading to belief sharedness. The consequences of exposure to linguistic bias, however, have yet to be shown and this is the aim of the present research program. The first study focuses on belief transmission, by determining if there is a direct causal effect from linguistic abstraction to individual impression formation. Results show that biased language transmits information about individuals but the communication context, specifically whom the message is about, is also important. Given this, it is likely that the content of the message will also affect the reception of biased language. The second study thus focuses on belief maintenance, by considering the relative effects of different levels of linguistic abstraction on pre-existing beliefs. Results were inconclusive, but may have been affected by methodological limitations. The third study addresses these limitations while focusing on belief formation, by measuring the impact of biased language in the absence of pre-existing beliefs. Recipients, in general, formed beliefs that corresponded to the biased language to which they were exposed. Together, these studies suggest that linguistic bias plays a role in belief sharedness as a mechanism through which cultural beliefs are transmitted and formed. Linguistic bias, however, must be understood within the specific communication context, which also independently affects reception.
Keywords: Linguistic bias; Biased language; Stereotypes; Prejudice; Language effects; Belief formation; Belief transmission; Culture; Belief maintenance; Cultural transmission; Language; Cultural dynamics; Implicit bias; Communication